PENGEMBANGAN HUTAN ADAT TARUPRAMANA DI DESA BATUBULAN KECAMATAN SUKAWATI KABUPATEN GIANYAR - Suniti, N.W.; Windia, W.P.; Purnawan, N.L.R.; Arthayani, I.A. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p10, 2018)
Community service activities is aimed at the development of indigenous forest in order to preserve the environment of indigenous Balinese culture and appeal of ecological tourism through the creation of nurseries, planting and plant arrangement taru pramana in Batubulan Sukawati Gianyar Regency. The method applied in community empowerment activities IbW (science and technology for the Region) is as follows: (1) Coordination and communication are participatory with farmers' groups to create a program from the planning, operational and evaluation; (2) Guidance for the perception and understanding of the innovations or programs implemented; (3) training to improve the skills of applied science and technology being transferred to the public; (4) Assistance is ongoing meetings between the chaperone with the target communities so that science and technology are transferred can be carried out independently by the community. The results obtained show that the dissemination of science and technology activities for the regions in Batubulan village, sub-district Sukawati, Gianyar can take place properly, the active participation of society and the adoption of science and technology is high. Active participation of partners in all activities of technology dissemination is high at 68%. Adoption of science and technology capabilities and partners' initiatives to produce seeds independently is quite high at 50%.